A systematic review and meta-regression of studies eliciting willingness-to-pay per quality-adjusted life year in the general population. (2nd January 2022) - Ye, Ziping; Ma, Jia; Liu, Fuyao; Wang, Chen; Zhou, Ziyang; Sun, Lihua
ABSTRACT: Objectives: From the demand-side perspective, the monetary value of one additional quality-adjusted life year (QALY) is estimated as willingness-to-pay per QALY (WTPQ). This study aims to summarize the methods and contexts of elicitation of willingness-to-pay per quality-adjusted life year (WTPQ) in the general population and to investigate the heterogeneity of WTPQ estimates. Methods: Meta-regression analysis was conducted using Comprehensive Meta-Analysis Software. Sensitivity analyses were undertaken by replacing the lowest and highest 5% and 2.5% of WTPQ by percentiles. Results: 33 studies with 102 WTPQ estimates were included. The overall mean and median WTPQ estimates are 1, 280, 002 and 44, 072, respectively. The meta-regressions demonstrated that types of health gain (quality of life or life length) and certainty of health outcomes are statistically significant factors. Furthermore, compared with online interviews, face-to-face interviews tend to yield lower WTPQ. Moreover, the declining trend of QALY gains and positive effect with statistical significance of the sample age were also noticed. Conclusion: For valid and representative values of WTPQ, future researchers should therefore take into consideration various scenarios and investigate both health gain with certainty and uncertainty, health gain from both life length and quality of life, and different size of QALY gains.